Strategy for Increasing 21st Century Skills Through Implementing Ibnu Sina's Thoughts at Cintawargi Elementary School, Tegalwaru District, Karawang Regency - Amirudin; Ferianto; Yadi Fahmi Arifudin; Achmad Junaedi Sitika; Agus Susanto; Akil; Ajat Rukajat; Puti Sahara; Putri Nur Afifah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The urgency of the 21st Century Skills educational development strategy in the world of education can be explained through several crucial aspects that influence the educational process and student preparation. Ibnu Sina has thoughts that are relevant to the challenges of the 21st century. Education development strategies based on Ibn Sina's thinking can help students develop the skills needed for access in the modern world, holistic skills development, increased creativity and innovation that stimulate students' imagination and innovation. This research aims to provide strategic policy recommendations in educational development through Ibnu Sina's thoughts at Cintawargi Elementary School, Tegalwaru District, Karawang Regency. This research uses qualitative descriptive methods, data collection techniques through observation, interviews and documentation as well as data analysis techniques using the Milles and Huberman method including data collection, data reduction, data presentation and verification.The research results showThe strategy to increase 21st Century Skills through the implementation of Ibnu Sina's thoughts at Cintawargi Elementary School, Tegalwaru District, Karawang Regency is implemented through several activities, namely: Increasing critical thinking skills, developing creative skills, improving communication skills, forming Ethics and Moral Values.